2018
DOI: 10.1002/lary.27719
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Multiple Hemorrhages Following Tonsil Surgery in Children

Abstract: Objectives/Hypothesis Although much is known about the incidence and risk factors for hemorrhage after tonsil surgery, the incidence and factors related to multiple episodes of hemorrhage are not well examined. Our objective was to identify risk factors that may contribute to multiple hemorrhages following tonsil surgery in children. Study Design Retrospective chart review. Methods A retrospective review was conducted of pediatric patients who experienced one or more hemorrhages following tonsillectomy/tonsill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
4
1
Order By: Relevance
“…Previous studies have suggested that older patients, those with recurrent tonsillitis, and those with a higher body mass index were more likely to have recurrent PTAH. 13,14 However, this was not reflected in our study, with no association found between age, gender, appearance of oropharynx, and recurrent PTAH. In addition, we did not find any association between abnormalities in hemoglobin concentrations and coagulation profile and risk of multiple bleeding episodes.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…Previous studies have suggested that older patients, those with recurrent tonsillitis, and those with a higher body mass index were more likely to have recurrent PTAH. 13,14 However, this was not reflected in our study, with no association found between age, gender, appearance of oropharynx, and recurrent PTAH. In addition, we did not find any association between abnormalities in hemoglobin concentrations and coagulation profile and risk of multiple bleeding episodes.…”
Section: Discussioncontrasting
confidence: 80%
“…12 Furthermore, choice of surgical technique, severity of first bleed, and NSAIDs use have not been found to increase the risk of recurrent PTAH. 12,14 The risk of recurrent PTAH is therefore difficult to predict for any given child.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there have been questions over the use of ibuprofen and other NSAIDs in posttonsillectomy patients. 34 While recent studies failed to find an association between NSAIDs and post-tonsillectomy bleeding, 35 2 studies reported that the administration of ibuprofen increases hemorrhage in the postoperative phase. 36,37 In regard with the use of antibiotic, our findings were in consistent with a recent, meta-analysis which showed that, the use of antibiotic did not reduce the incidence posttonsillectomy bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been questions over the use of ibuprofen and other NSAIDs in post-tonsillectomy patients. 34 While recent studies failed to find an association between NSAIDs and post-tonsillectomy bleeding, 35 2 studies reported that the administration of ibuprofen increases hemorrhage in the postoperative phase. 36,37…”
Section: Discussionmentioning
confidence: 99%